Design, Synthesis, and Biological Evaluation of 3-Substituted-Indolin-2-One Derivatives as Potent Anti-Inflammatory Agents - Lee, Sung Jin; Lee, Sang Hyuk; Lee, Heesu; Shin, Myoung-Sook; Jae Wook Lee (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
This study aimed to synthesize and evaluate the anti-inflammatory activity of 3-substituted-indolin-2-one derivatives. Cell viability of 3-substituted-indolin-2-one derivatives was measured with the EZ-Cytox reagent; interleukin (IL)-6, tumor necrosis factor (TNF)-α, and inducible NOS mRNA levels were measured using Taqman qRT-PCR; pro-inflammatory cytokine IL-6 and TNF-α levels were determined using ELISA kits; the phosphorylation of Akt, JNK, ERK, p38, p65, and IκB protein levels were measured by immunoblotting. Among the nineteen 3-substituted-indolin-2-one derivatives synthesized, 3-(3-hydroxyphenyl)-indolin-2-one showed the highest anti-inflammatory activity, inhibiting the nitric oxide production related to inflammation, suppressing the production of TNF-α and IL-6 in a concentration-dependent manner and mRNA expression. Moreover, 3-(3-hydroxyphenyl)-indolin-2-one significantly inhibited lipopolysaccharide (LPS)-induced signal pathways such as the Akt, MAPK, and NF-κB signaling pathways. Our findings revealed that a 3-substituted-indolin-2-one derivative, 3-(3-hydroxyphenyl)-indolin-2-one, possesses excellent anti-inflammatory activity and can be considered for future research.